Prevalence of white coat and coincidental hypertension among preoperative patients - Khan, Ahsan Habib; Banik, Debabrata; Ahmed, Naorin; Mahmud, Nahin; Naim, Nazmul Huda; Fahad, M. (International Journal of Research in Medical Sciences, 2026)
Background: Hypertension is a major global health concern with significant perioperative implications. White coat hypertension (WCH) and coincidental hypertension (CH) are undiagnosed blood pressure patterns that affect surgical outcomes, sometimes causing unnecessary interventions or delays. This study determined the prevalence of WCH and CH during preoperative assessment at the BMU and associated clinical factors. Methods: This cross-sectional study was conducted at the department of anesthesia, analgesia and intensive care medicine, Bangladesh Medical University (BMU), Dhaka, Bangladesh, from April 2024 to March 2025 among 2,084 adults who underwent elective surgery at the preoperative assessment unit (PAU). Patients ≥18 years were purposively sampled, blood pressure was measured, and patients were classified as known hypertensive, normotensive, or undiagnosed. Undiagnosed cases were followed up to pre-induction and categorized as white coat or coincidental hypertension. Data were analyzed using SPSS version 27.0. Results: Among the 2,084 preoperative patients, 445 (21.4%) were hypertensive, 1,561 (74.9%) were normotensive and 78 (3.7%) had previously undiagnosed hypertension, including 26 (33.3%) with white-coat hypertension and 52 (66.7%) with coincidental hypertension. Patients with coincidental hypertension were older, had more comorbidities, experienced more surgical cancellations (11.5% versus 0%; p=0.049), and had significantly higher systolic and diastolic blood pressure throughout the follow-up than those with white coat hypertension (all p<0.05). Conclusions: Undiagnosed hypertension is common in the preoperative setting, with coincidental hypertension being more prevalent than white coat hypertension and associated with higher perioperative risk and surgical postponement.